Drug treatment of Type 2 diabetes: its cost is significantly associated with HbA1c levels - Elgart, Jorge Federico (2019)
Aims: to examine the relationship between costs of hyperglycemia drug treatment and glycemic control among people with type 2 diabetes (T2D). Methods: This observational study utilized data from the QUALIDIAB database on 3,452 T2D patients seen in Diabetes Centers in Argentina. Patients were classified according to their HbA1c value into two groups: On Target (OT; HbA1c≤7%), and Not on Target (NOT; HbA1c>7%); within each category we considered clinical and metabolic indicators, as well as type of hyperglycemia treatment. Monthly expenditure on drugs was estimated by micro‐costing. Multivariable regression analysis was used to evaluate the association between cost of hyperglycemia treatment and HbA1c values. Results: 48.9% of the participants have HbA1c on target values. Overall monthly per capita costs of this treatment increased significantly (134%) in the NOT group. Multivariable regression analysis showed that expenditure for hyperglycemia drugs treatment was significant associated with glycemic control (OR:0.705), diabetes duration (OR:1.017), systolic blood pressure (OR:1.006), and treatment of T2D (OR:2.622). Conclusions: HbA1c not on target significantly increases drugs monthly cost of hyperglycemia treatment in people with T2D in a country with an emerging market economy. This article is protected by copyright. All rights reserved.